Semantic fields of German loanwords in Slovenian - Šekli, Matej (Jezikoslovni zapiski, 2018)
This article discusses the semantic fields of German loanwords in Slovenian. Slovenian- -German language contact is placed into the broader context of Slavic-Germanic language contacts. On the basis of phonological characteristics of German loanwords in Slovenian, the relevant geolect (i.e. the geographic variant), the sociolect (i.e. the social variant), and the chronolect (i.e. the temporal variant) of the German source is determined. Both phonological and semantic analyses of German loanwords in Slovenian help expose the spheres of human culture in which German culture exerted its influence on Slovenian culture throughout various historical periods.